PROFIL GC-MS DAN BIOAKTIVITAS EKSTRAK MINYAK DAUN CENGKEH (Syzygium aromaticum) TERHADAP ULAT GRAYAK Spodoptera frugiperda (GC-MS PROFILING AND BIOACTIVITY OF EXTRACTS CLOVE LEAF OIL (Syzygium aromaticum) AGAINST FALL ARMYWORMS Spodoptera frugiperda) - Sitohang, Mikael; Jayuska, Afghani; Hernowo, Kukuh; Alimuddin, Andi Hairil; Aritonang, Anthoni Batahan (Indonesian Journal of Pure and Applied Chemistry, 2024)
Clove leaf essential oil can be used as a natural insecticide to control pests. Essential oil obtained by steam distillation produces essential oil with a yield of 1.03%. The essential oil obtained was then analyzed using a GC-MS tool where the aim was to separate the mixture of compounds and identify the compounds contained in clove leaf essential oil. The results of GC-MS analysis of clove leaf essential oil shoved 6 compounds whose similarity was above 84%, where the main compounds were eugenol (74.28%), Î²-Caryophellene (20.49%), Î±-Caryophellene (2.32%), Caryophellene oxide (2.26%). The essential oils were then tested for mortality and antifeedant activity against 3rd larva S. frugiperda. Concentrations of 0.1%, 0.3%, 0.5%, 0.7% and 0.9% v/v the essential oil caused 43.44%, 56.66%, 70%, 76.77%, and 86.66% mortality on to tested larva. The probit analysis data the mortality resulted LC50 value of 0.58%. Antifeedant concentrations of 0.37% and 0.58% v/v or equivalent to LC25 and LC50 can reduce 42.41-71.96% of the preferred method and 66.46-86.59% of the non-optioned method.